Densification and biocompatibility of sintering 3.0 mol% yttria-tetragonal ZrO2 polycrystal ceramics with x wt% Fe2O3 and 5.0 wt% mica powders additive. Issue 2 (1st February 2017) - Wang, Cheng-Li; Lan, Ting-Hsun; Tzeng, Cheng-Wei; Chang, Chih-Chi; Lin, Tzu-Chan; Ko, Horng-Huey; Hwang, Weng-Sing; Huang, Hong-Hsin; Yen, Feng-Lin; Wang, Moo-Chin
Abstract: The densification and biocompatibility of sintered 3.0 mol% yttria-tetragonal zirconia polycrystal (3Y-TZP) ceramics, with X wt% Fe2 O3 and 5.0 wt% mica powders (denoted by 3Y-TZP: X-5.0 wt% mica) have been studied. When the pellets of 3Y-TZP: X-5.0 wt% mica were sintered at 1300 °C for 1 h, the relative shrinkage increases from 19.20–19.43% with the X increased from 0.3 to 1.0. The relative shrinkage of pellets containing 1.0 wt% Fe2 O3 ( X =1.0) increased from 19.43–19.59% when sintering temperatures were raised from 1300 °C to 1450 °C. X-ray diffraction results show that the pellets of 3Y-TZP: X-5.0 wt% mica sintered at 1400 °C for 1 h only contained single phase of tetragonal ZrO2 (t-ZrO2 ). When the sintering temperature was higher than 1400 °C, the Vickers microhardness was greatest in the pellets with X =0.5. Within pellets with the same Fe2 O3 content, the dominant wavelength ( λ d ) was only slightly different for pellets sintered at 1300 °C and those sintered at 1450 °C. The results of the materials were evaluated in vitro cytotoxicity tests reveals that the powders and sintered pellets are safe materials. The oral mucosa irritation tests did not find erythema or histopathological change including normal epithelium, and was free from leucocyte infiltration, vascular congestion and oedema.